Two-year prognosis after residential treatment for patients with alcohol dependence: three chief guidelines for sobriety in Japan - Cho T; Negoro H; Saka Y; Morikawa M; Kishimoto T (Neuropsychiatric Disease and Treatment, 2016)
Tetsuji Cho,1,2 Hideki Negoro,3 Yasuhiro Saka,1 Masayuki Morikawa,1,2 Toshifumi Kishimoto2 1Mie Prefectural Mental Care Center, Tsu-Shi, Mie, 2Department of Psychiatry, Nara Medical University School of Medicine, Kashihara, Nara, 3Faculty of Education, Nara University of Education, Nara, Japan Background: In Japan, the three chief traditional guidelines for sobriety (3CGS) are regular medical checkups, participation in self-help groups, and pharmacotherapy with antidipsotropics. However, the official record of the origins of 3CGS is not clear. The aim of this current study was to assess 3CGS by an examination of the prognosis of patients with alcohol dependence 2 years after their discharge from a residential treatment program. Subjects and methods: The association between subjects’ abstinence from alcohol and their regular medical checkups, participation in self-help groups, and treatment with antidipsotropics were prospectively examined. Two years after discharge, the relationship between the 3CGS compliance and abstinence rates was investigated as the primary outcome. In addition, the following were examined as secondary outcomes: the time taken till the first drink after discharge, whether the participants were readmitted to residential treatment, the number of days to readmission, the number of heavy drinking days, and recovery. Results: A total of 98 patients participated. The perfect and partial abstinence rates for patients who followed all the principles of 3CGS were significantly higher than those for patients who followed no guidelines (P<0.05 and P<0.01, respectively). The perfect abstinence rates for patients who had continued attending checkup sessions (P<0.001) and who were taking antidipsotropics (P<0.05) were significantly higher than those for patients who did not follow these components of 3CGS. However, the perfect abstinence rates were not higher for patients who had continued to participate in self-help groups. In addition, the perfect abstinence rate was statistically associated with regular medical checkups (adjusted odds ratio =5.33, 95% confidence interval =1.35–21.0) and participation in self-help groups (adjusted odds ratio =3.79, 95% confidence interval =1.17–12.3). Conclusion: This study, reports the effectiveness of 3CGS for the first time. The recovery rate of alcoholics 2 years after discharge from residential treatment was examined. However, due to the chronic nature of alcoholism, further studies are required to investigate the efficacy of 3CGS beyond 2 years. Keywords: alcohol dependence, three chief guidelines for sobriety (3CGS), disulfiram, self-help group, recovery